THE EVOLUTION OF THE LEGISLATIVE PROVISION OF PENAL DIFFERENTIATION AND INDIVIDUALIZATION OF SENTENCING - Abrahamyan, Roza (State and Law, 2023)
The evolution of the legislative provision of penal differentiation and individualization of sentencing The present article highlights the penitentiary differentiation and individualization of the execution of punishments, as well as the evolution of its fixation. Under the influence of democratization of public life, and the adoption of a full legal concept of human rights , as well as under the condition of the independence of the RA one of the legal reforms became the review of the penal policy and the reforms of the legislation. Also, the article aims to introduce the new Penal Code of RA adopted on June 15,2022 which inproved the legal technique of fixing and legal regulation of the principles of penal law in the penal legislation.
Keywords: penitentiary system; the legal status of prisoners; the classification of prisoners; re-socialization of prisoners